DL-3-n-butylphthalide (NBP) alleviates poststroke cognitive impairment (PSCI) by suppressing neuroinflammation and oxidative stress - Zhang, Hui; Wang, Laifa; Yang, Yongping; Cai, Chuanhai; Wang, Xueqin; Deng, Ling; He, Binsheng; Zhou, Wenhu; Cui, Yanhui (Frontiers in Pharmacology, 2023)
Currently, the recovery of cognitive function has become an essential part of stroke rehabilitation. DL-3-n-butylphthalide (NBP) is a neuroprotective reagent and has been used in stroke treatment. Clinical studies have confirmed that NBP can achieve better cognition outcomes compared with controls. In this study, we aimed to investigate the influences of NBP on cognitive function in acute ischemic stroke (AIS) rat model. Our results showed that NBP profoundly improved neurological function by decreasing neurological score, reducing cerebral infarct area and enhancing cerebral blood flow (CBF). NBP potently alleviated poststroke cognitive impairment (PSCI) by attenuating depression-like behavior, improving learning and memory capacity and social cognition in AIS rats. NBP distinctly suppressed the activation of microglia and astrocytes and improved neuron viability in the ischemic brain. NBP inhibited the expression of inflammatory cytokines including IL-6, IL-1β and TNF-α by targeting NF-κB/iNOS pathway. Furthermore, NBP downregulated cerebral oxidative stress factors including ROS and MDA by targeting Keap1/Nrf2 pathway. The current study revealed that NBP treatment improved neurological function and ameliorated cognitive impairment in AIS rats possibly by synergistically suppressing inflammation and oxidative stress.